Paternal High Fat Diet and Exercise Regulate Sperm miRNA to Alter Placental Inflammation and Nutrient Transporter Expression in a Sex-Dependent Manner. (29th May 2020) - Larson, Kate; Bundy, Amy; Roemmich, James
Abstract: Objectives: We have shown that male offspring (F1) of fathers (F0) fed a high fat (HF) diet and exercised had greater skeletal muscle insulin signaling and reduced T2DM risk compared to fathers fed HF diet and remain sedentary. The current study extends this work by hypothesizing that F0 HF diet and exercise regulate F1 T2DM risk by early alterations in epigenetics of placental tissue growth via changes in sperm miRNA expression. Methods: To test these hypotheses, three-week old male C57BL/6 mice were fed a normal-fat (NF) diet (16% fat) or a HF diet (45% fat) and assigned to either voluntary wheel running exercise or cage activity for 3 months prior to mating with NF diet fed dams. F0 sperm and placental tissue samples were collected to determine changes in placental and fetal weights, placental gene expression, and F0 sperm miRNA expression. Results: F0 sperm miRNA 193b expression was decreased while miRNA 204 was increased by paternal exercise. Protein expression of di-methylated histone 3 lysine 9 was decreased with F0 HF diet. Placental and fetal tissue weights were decreased by F0 HF diet in F1 males while no changes in the F1 females. Placental proinflammatory cytokine mRNA expression, including IL-1 beta and TNF-alpha, was reduced by paternal exercise while nutrient transporter mRNA expression was decreased by paternal HF diet only in the placentae of F1 females. Treatment of primary placental cell with miRNA 193 inhibited TNF-alpha mRNA expression. In addition, treatment of the same cells with TNF-alpha increased SLC6a19. Moreover, paternal exercise increased body weight at weaning in a female offspring. Conclusions: These results demonstrate that placental tissue weight, placental nutrient transporter gene expression and fetal weights are altered by paternal exercise while placental inflammatory gene expression are influenced by paternal exercise in offspring in a sex-specific manner. Funding Sources: This work was supported by USDA ARS Project #3062–51, 000-054–00D.